Crimea and the “Emperors of Solkhat” in 1400–1430: A Chronology of the Reign and the Status of the Rulers - V.P. Gulevich (Золотоордынское обозрение)
The first third of the 15th century was difficult and the most important period in formation of the Crimean Khanate. Despite the importance of the Crimea for the Golden Horde, it was rather peripheral district. The impossibility to control the situation on the peninsula has led to the fact that the Emir Idegei and his khans returned to the practice started by Toktamysh Khan at the end of the 14th century and allowed a local Chingizid Khan Bek-Sufi (from the genus of Tuka-Timur) to rule in the Crimea. As a ruler of the Crimean Ulus, Beck-Sufi Saray recognized the power of the Saray khans, whose governors were constantly in Solkhat. Khan Dawlet Berdi, brother of Beck-Sufi Khan, also received the approval from the Ulugh Muhammad Khan to rule in the Crimea, but tried to seize the power in the Golden Horde and lost. Thus, there is no reason to remove the date of the emergence of the Crimean khans and Crimean Khanate itself from 1442 to 1420. On the contrary to the accepted view of the active intervention of the Lithuanian Grand Duke Vytautas in the history of the Golden Horde, an objective analysis of the sources for the period of 1400–1430 does not confirm this.